Phytochemical Constituents of Some Vegetables - Howlader, Md Abu Hasan; Iqbal, Md Shamim; Islam, SM Sirajul; Quader, MA (Dhaka University Journal of Science, 2013)
Alkaloids, terpenoids, tannins, saponins, phlobatannins, flavonoids, steroids, cardiac glycosides, sugar molecules, and amino acid distribution in four vegetables of Bangladesh origin belonging to the family of Cucurbitaceae were assessed and compared. The vegetables investigated were Luffa acutangula (Jhingga), Luffa cylindrica (Dhundul), Trichosanthes anguina (Chichingga) and Tricosanthes dioica (Potol). DOI: http://dx.doi.org/10.3329/dujs.v61i2.17060 Dhaka Univ. J. Sci. 61(2): 147-151, 2013 (July)